Sistem Berbasis Aturan Untuk Menentukan Tingkat Gangguan Manic Depression - Guruh Wijaya; Sri Kusumadewi; Hepi Wahyuningsih (INFORMAL: Informatics Journal, 2017)
Manic Depression Disorder is often a trigger for people to do things beyond their normal behavior, can even lead to extreme behavior. There are several scales that can be used to indicate the extent of this disturbance. The most commonly used scales are the Depression Trend (BDI), the Anxiety Scale (TMAS), and the Suicidal Tendency Scale (SIBD). In this research will be built case-based system to determine the level of disturbance Manic Depression by using scale BDI, SIBD and TMAS. The subjects used were the inmates of Class IIA Jember by using a rule-based expert system. The rules are derived from literature studies and input from experts. To increase flexibility, the system is designed web-based. Expert systems are offered as second choice after specialist medical personnel. The results of this study are expected to be a reference for prisons and related parties to develop problem-based intervention programs, especially those related to prevention and curative programs in addressing these psychological problems